2007
DOI: 10.1002/pros.20710
|View full text |Cite
|
Sign up to set email alerts
|

The toll‐like receptor pathway: A novel mechanism of infection‐induced carcinogenesis of prostate epithelial cells

Abstract: Our study has identified a unique mechanism that describes how components of pathogens common in the urinary system may contribute to the malignant transformation of benign prostate epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 17 publications
6
101
0
Order By: Relevance
“…Moreover, the induction of TLRs on tumor cells may directly promote proliferation, such as in human prostate cancer and in head and neck cancer. This reaction is time-and dose-dependent and is reflected by NF-κB induction and the subsequent upregulation of oncoprotein c-Myc [64,65]. However, there are studies suggesting a protective role of TLR stimulation and possible therapeutic options exploiting TLR ligation.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…Moreover, the induction of TLRs on tumor cells may directly promote proliferation, such as in human prostate cancer and in head and neck cancer. This reaction is time-and dose-dependent and is reflected by NF-κB induction and the subsequent upregulation of oncoprotein c-Myc [64,65]. However, there are studies suggesting a protective role of TLR stimulation and possible therapeutic options exploiting TLR ligation.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…Several studies indicated that these infectious agents may elicit an immune response, creating a cytokine tissue environment that leads to chronic inflammation, DNA damage, cell proliferation, angiogenesis and ultimately prostate cancer (32)(33)(34)(35)). An in vitro study suggested that components of viral and other infectious agents may shift the balance towards altered homeostasis in cells that have already deviated from normal gene expression and may thus play a role in malignant transformation (36). Several epidemiological studies evaluated the association between herpes virus infection and prostate cancer risk, although results were inconsistent (9,14,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori acting through TLR2/TLR9 on gastric epithelial cells activated both Src and NF-kB, resulting in an increased expression of cyclooxygenase-2 (Cox-2), which may contribute to gastric cancer progression (Chang et al, 2004). The triggering of TLR4 and TLR9 on prostate cancer cells has also been shown to promote tumour cell proliferation through increased NF-kB activation (Kundu et al, 2008).…”
mentioning
confidence: 99%